Elucidating the mechanistic association of xylene inducing non-small cell lung cancer through network toxicology and molecular docking analysis - Hongquan Chen; Xiangpeng Chen; Weibin Lin; Qing Chen; Renxi Lin; Mingfang Zhang; Yuanlin Qi (PLoS ONE, 2026)
Xylene is a common industrial solvent that includes three isomers: o-xylene, m-xylene, and p-xylene. Long-term exposure to low doses of xylene in the environment has been linked to a higher risk of lung cancer. However, the molecular mechanisms behind this link are still not fully understood. In this study, we used a combination of network toxicology and molecular docking to investigate how xylene may contribute to the development of non-small cell lung cancer (NSCLC). We first identified 115 potential target genes related to xylene exposure by searching several public databases, including CHEMBL, STITCH, GeneCards, and OMIM. Further screening using the STRING platform and Cytoscape analysis highlighted five core targets: IL1A, H3C13, ITGAM, CCR5, and COMT. We utilized scRNA-seq data to analyze the expression patterns of core targets across distinct cell subpopulations, the majority of core targets were expressed in immune cells. We then performed GO and KEGG pathway enrichment analysis. These results showed that the five target genes are mainly involved in cancer-related pathways, such as ECM-receptor interaction, focal adhesion, chemical carcinogenesis, and the PI3K-Akt signaling pathway. Molecular docking results confirmed that xylene isomers have strong binding affinities with the proteins encoded by these genes. This suggests that xylene may disrupt important cellular signals and promote tumor growth. In conclusion, our study provides new insight into how xylene might cause NSCLC at the molecular level. It also shows the usefulness of network toxicology in evaluating health risks from environmental chemicals. These findings may help guide future efforts in prevention and treatment strategies.